Superiority of CRP-albumin-lymphocyte index as a prognostic biomarker for patients with gastric cancer - Zhang, Heyang; Shi, Jinyu; Xie, Hailun; Liu, Xiaoyue; Ruan, Guotian; Lin, Shiqi; Ge, Yizhong; Liu, Chenan; Chen, Yue; Zheng, Xin; Song, Mengmeng; Yang, Ming; et al. (Nutrition (Burbank, Los Angeles County, Calif.), 2023)
•Patients with gastric cancer and a high C-reactive protein–albumin–lymphocyte (CALLY) index have better overall survival.•The CALLY index could be used as an independent prognostic factor for patients with gastric cancer.•The nomogram combining TNM stage, body mass index, and the CALLY index has better prediction ability. The new C-reactive protein (CRP)-albumin-lymphocyte (CALLY) index is an immune nutrition scoring system based on serum CRP) serum albumin, and lymphocyte counts. The aim of this study was to verify the prognostic value of the CALLY index in patients with gastric cancer and to evaluate the superiority of this new system. We retrospectively analyzed the data of patients with gastric cancer who were followed up from the INSCOC database between May 2013 and December 2018. Through simple random sampling, patients with gastric cancer were placed into one of two groups: the training group (n = 684) or the verification group (n = 290) in a ratio of 7:3. Correlation analysis, Kaplan-Meier method, and cubic spline function were used to analyze the relationship between the CALLY index and overall survival (OS) in these patients. Based on the results of Cox regression analysis of the training cohort, a nomogram model for predicting 1 -, 2 -, 3-, and 5-y OS was established and verified internally. The prediction accuracy and benefit of the nomogram in gastric cancer were evaluated by calibration and clinical decision curve and compared with the traditional TNM gastric cancer staging system. The CALLY index was negatively correlated with the age of patients with gastric cancer (men, r = –0.1; women, r = –0.1), but positively correlated with body mass index (BMI; men, r = 0.063; women, r = 0.058), and the cutoff value of the CALLY index was determined as 1.12. The OS of patients with gastric cancer and a CALLY index >1.12 was significantly higher than that of patients with gastric cancer and a CALLY index ≤1.12 (P < 0.0001). There was an L-shaped dose-response relationship between the CALLY index and OS in patients with gastric cancer, and age, TNM stage, surgical treatment, chemotherapy, BMI, and the CALLY index were significantly correlated with the prognosis of patients with gastric cancer. Tumor TNM stage, BMI, and the CALLY index were independent risk factors affecting the prognosis of patients with gastric cancer. The CALLY index was a protective factor in the following patient factors: diagnosis of gastric cancer; <65 y of age; male; TNM 3 stage; BMI 18.5 to 23.9 kg/m2; smoker; consumer of alcohol; no radio- or chemotherapy; surgery; presence of diabetes, hypertension, or both; no family history of cancer; experienced a significant interaction with chemotherapy and surgery. A nomogram based on TNM staging, BMI, and the CALLY index has good predictive ability and clinical application value. Compared with traditional TNM staging systems, the nomogram has better resolution and accuracy in predicting 1 -, 2 -, 3-, and 5-year OS. The CALLY index can be used as an independent prognostic factor for patients with gastric cancer, and constructs a nomogram prediction model combining TNM staging, BMI, and CALLY index, which yields better predictions than traditional TNM staging.